Changes in topsoil carbon stock in the Tibetan grasslands between the 1980s and 2004 - YUANHE YANG; JINGYUN FANG; PETE SMITH; YANHONG TANG; ANPING CHEN; CHENGJUN JI; HUIFENG HU; SHENG RAO; KUN TAN; JIN‐SHENG HE (Global Change Biology, 2009)
Climate warming is likely inducing carbon loss from soils of northern ecosystems, but little evidence comes from large‐scale observations. Here we used data from a repeated soil survey and remote sensing vegetation index to explore changes in soil organic carbon (SOC) stock on the Tibetan Plateau during the past two decades. Our results showed that SOC stock in the top 30 cm depth in alpine grasslands on the plateau amounted to 4.4 Pg C (1 Pg=10 15 g), with an overall average of 3.9 kg C m −2 . SOC changes during 1980s–2004 were estimated at −0.6 g C m −2 yr −1 , ranging from −36.5 to 35.8 g C m −2 yr −1 at 95% confidence, indicating that SOC stock in the Tibetan alpine grasslands remained relatively stable over the sampling periods. Our findings are nonconsistent with previous reports of loss of soil C in grassland ecosystems due to the accelerated decomposition with warming. In the case of the alpine grasslands on the Tibetan Plateau studied here, we speculate that increased rates of decomposition as soils warmed during the last two decades may have been compensated by increased soil C inputs due to increased grass productivity. These results suggest that soil C stock in terrestrial ecosystems may respond differently to climate change depending on ecosystem type, regional climate pattern, and intensity of human disturbance.